When do we see that others misrepresent how they feel? detecting deception from emotional faces with direct and indirect measures - Mariëlle Stel; Eric van Dijk (Social Influence, 2018)
Nonverbally-expressed emotions are not always linked to people’s true emotions. We investigated whether observers’ ability to distinguish trues from lies differs for positive and negative emotional expressions. Participants judged targets either simulating or truly experiencing positive or negative emotions. Deception detection was measured by participants’ inference of the targets’ emotions and their direct judgments of deception. Results of the direct measure showed that participants could not accurately distinguish between truth tellers and liars, regardless which emotion was expressed. As anticipated, the effects emerged on the indirect emotion measure: participants distinguished liars from truth tellers when inferring experienced emotions from negative emotional expressions, but not positive emotional expressions.